(untitled) (Revista Brasileira Multidisciplinar, 2026)
Chronic Myeloid Leukemia (CML) is a hematological malignancy that historically resulted in low survival rates until the advent of Tyrosine Kinase Inhibitors (TKIs). However, therapeutic success heavily relies on patient adherence and the safety of these therapies. Monitoring the use of TKIs allows for the early identification of potential reasons for therapeutic failure, enabling immediate management. In this context, an integrative literature review was conducted to answer the question: What does the literature discuss about monitoring the use of TKIs in patients with CML? The databases included were PubMed/MEDLINE, Embase and Scopus (Elsevier), Web of Science (Clarivate Analytics), SciELO, LILACS, Cochrane Library, and CINAHL (EBSCO). Out of 325 identified documents, 18 met the inclusion criteria. The analyzed studies demonstrated consistency regarding the monitoring of therapy effectiveness, especially concerning the average time required to achieve treatment goals. However, divergent points were identified in terms of molecular response and the appropriate timing for switching TKIs. Few documents explored adherence in depth. Regarding safety, the main focus was on key adverse reactions, with limited discussion on their management or the risks of drug interactions. The monitoring of these treatments enables the early identification of issues that may compromise survival rates and disease-free remission. Thus, the information presented here can support professionals in the care of these patients, contributing to achieving better therapeutic outcomes.